A user-orientated electronic laboratory notebook for retrieval and extraction of provenance information for EUROCHAMP-2 - Zaki Z.M.; Dew P.M.; Haji M.H.; Lau L.M.S.; Rickard A.; Young J. (2024)
Indexed by Scopus